FOSTERING CREATIVE AND AESTHETIC THINKING IN FINE ARTS EDUCATION THROUGH INNOVATIVE METHODS - Ismoilov Otabek Shavkat o‘g‘li (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article examines innovative approaches to developing students’ creative and aesthetic thinking in fine arts education. It highlights the use of interactive lessons, project-based learning, digital tools, and student-centered pedagogy to enhance visual thinking, artistic perception, and engagement with art. The study emphasizes creating a supportive and creative learning environment that encourages originality, experimentation, and critical evaluation of artworks.